Comparing Malangan And Mataraman Javanese Dialect: A Case Study in The Border Area of Malang And Blitar - Roosi Rusmawati; Ismatul Khasanah; Ismi Prihandari; Khilmi Mauliddian (Universitas Cokroaminoto Palopo, 2023)
This study aims to observe differences in the Javanese dialect of Malangan and Mataraman and the factors that influence the phenomenon, as both dialects are spoken in the border region of Malang and Blitar. The method used in this research is qualitative, which is to provide a general description of a situation as clearly as possible without any treatment of the object under study. This research is a sociolinguistic study based on the language phenomenon that occurs in the community in the cultural border area of a ​​language, especially regarding the form of dialect differences that occur. The results suggest that the differences lie in the description markers in Ngoko Javanese. Such phenomenon is observed based on various words spoken in various situations in both regions. In addition, despite the differences of the description markers between the two dialects, the meanings behind them are not significantly different. As for the factors that make the differences between the Malangan and Mataraman dialect spoken in the Malang and Blitar border areas, they are divided into four: speakers’ habits, self-identity, region/geography, and feeling of having a different dialect/language.